GRAMMAR IN TEFL: A CRITIQUE OF INDONESIAN HIGH SCHOOL TEXTBOOKS - Peter Collins (TEFLIN Journal: A publication on the teaching and learning of English, 2006)
Abstract: The aim of this paper is to critically assess the presentation of English grammar in textbooks used in secondary schools in Indonesia. The influence of the Communicative Approach is in evidence in the books examined, and yet the importance of explicit grammar instruction is not ignored, reflecting the view of many today that grammatical forms cannot be successfully learnt merely on the basis of comprehensible input. Despite recognition of its central role, the grammar instruction presented in the textbooks invites questions as to its linguistic adequacy and accuracy. Writers often seem unwilling to take on board the insights recorded in the influential and authoritative descriptive grammars of recent years, continuing to accept tacitly the principles exposed in Traditional Grammar.